Husband’s support on the use of Intra Uterine Device (IUD) and implant contraceptives among Indonesian couples - Retno Heru Setyorini; Era Revika; Riadini Wahyu Utami; Oktriyanto Oktriyanto; Mardiana Dwi P (Universitas Aisyiyah Yogyakarta, 2020)
The involvement of men in family planning has an important role in making decisions related to the use of contraception. This study aimed to determine the effect of husband’s support on the use of IUDs and Implant contraception among Indonesian couples. This is an analytic survey with a cross-sectional approach. The sample was selected by using the Slovin formula, resulted 398 respondents. Sampling was carried out using accidental sampling. Data collection was carried out using a questionnaire. Validity and reliability tests were carried out using Pearson's product-moment and Cronbach's alpha. Results analysis of the study was carried out by multiple logistic regression. 251 (63.1%) husbands were supporting the use of IUDs and Implant contraception as much as 147 (36.9%) others did not support the use of both contraceptives. The results of multiple logistic regression analysis are OR = 7,713; p = 0,0001 Husband's support influences the use of IUDs and Implant contraception.